Effectiveness of an Intervention based on Peplau’s Model on Health Literacy among Nurses Who Smoke: A Quasi-Experimental Study - Achmad Djojo; Suhariyanto Suhariyanto; Lily Yuniar; Arsad Suni; Efi Riani; Yogi Ervandi; Sepni Walvri; Anggie Aprizal; Rr Tutik Sri Hariyati; Hanny Handiyani (Universitas Airlangga, 2020)
Introduction: : Lack of health literacy for smoking nurses has worsened image of nursing services. The role of leader can be a support in increasing behavior change of nurses who smoke. The aimed to find out health literacy of smokers in nursing staff through interpersonal role of the head of the room by intervention based on Peplau’s model.Methods: A quasi-experimental research with a pre-and post-control group design, using modification questionnaire of knowledge and behavior. The target population was nurses living in Singkawang who smoke in a hospital. Sample was 35 respondents for each group (controlling group and intervention group) using purposive sampling. Dependent variable is health literacy among nurses who smoke and independent variable is intervention based on Peplau’s model. Intervention is in the form of a guide module consisting of strengthening health literacy (health awareness, self-reflection, cognitive competence and behavioral interpersonal relationships in the head of the room) and will be implemented to nurses who smoke. Analysis data for bivariate used paired t – test and for multivariate used the McNemar test.Results: The research showed that the difference before and after intervention was 2.23 (p = 0.001) and control group was 8.00 with a default value of 0.870 deviation. The results showed a significant increase in health literacy in nurse smokers through the role of interpersonal head nurse (p=0.001).Conclusion:Role of head of room in interpersonal relationship with Peplau’s model affects the health literacy of nursing staff who smoke.